2013
DOI: 10.1074/jbc.m112.381343
|View full text |Cite
|
Sign up to set email alerts
|

From Macrophage Interleukin-13 Receptor to Foam Cell Formation

Abstract: Background: CD36, a macrophage receptor critical for oxidized lipid uptake during atherogenesis, is up-regulated after IL-4/IL-13 stimulation. Results: The mechanism whereby integrin ␣ M ␤ 2 inhibits CD36 gene expression and related foam-cell formation is elucidated. Conclusion: Activated integrin ␣ M ␤ 2 suppresses CD36-mediated lipid uptake by blocking Tyk2-and Jak2-mediated signaling pathways. Significance: ␣ M ␤ 2 integrin regulation of CD36 expression and function reveals a new mechanism that may control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…They form a cell surface receptor (integrin α M ß 2 ) that mediates phagocytosis, migration and chemotaxis [41]. In addition, talin and cysteine proteinase cathepsin X/Z (CTSZ) were also up-regulated in IL4-stimulated macrophages.…”
Section: Functional Analysis Of Lps-and Il4-up-regulated Proteinsmentioning
confidence: 99%
“…They form a cell surface receptor (integrin α M ß 2 ) that mediates phagocytosis, migration and chemotaxis [41]. In addition, talin and cysteine proteinase cathepsin X/Z (CTSZ) were also up-regulated in IL4-stimulated macrophages.…”
Section: Functional Analysis Of Lps-and Il4-up-regulated Proteinsmentioning
confidence: 99%
“…Co-evolution between Mac-1 and IL-13R␣1-Recently, Yakubenko et al (9,14) reported that Mac-1 suppresses IL-13-induced JAK/STAT activation in macrophages and reduces their uptake of oxLDL in vitro; however, the molecular mechanism underlying this unique regulatory function of Mac-1 is not yet established. To identify potential biological partners that confer the inhibitory activity of Mac-1 toward IL-13-induced macrophage activation, we used an unbiased informatics-based method, termed Mirrortree (28 -30), to predict protein-protein interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies demonstrated that Mac-1, a major leukocyte integrin expressed on macrophages and macrophage-derived foam cells, exhibits potent inhibitory activities toward JAK/STAT activation in IL-13-stimulated macrophages, which reduces their ability to uptake oxLDL in vitro (9,14). However, the molecular mechanism by which Mac-1 inhibits IL-13 signaling in macrophages is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations